Enantioselective deprotometalation of N, N-dialkyl ferrocenecarboxamides using metal amides. (4th September 2019) - Hedidi, Madani; Dayaker, Gandrath; Kitazawa, Yu; Yoshii, Tatsuya; Kimura, Mutsumi; Erb, William; Bentabed-Ababsa, Ghenia; Chevallier, Floris; Uchiyama, Masanobu; Gros, Philippe C.; Mongin, Florence
Abstract : Our attempts to deprotometalate N, N -dialkyl ferrocenecarboxamides enantioselectively by using chiral lithium or lithium–zinc dialkylamides are reported. Abstract : N, N -Diisopropylferrocenecarboxamide can be enantioselectively deprotometalated by combining butyllithium with (−)-sparteine in diethyl ether at low temperature. It is of interest to identify conditions that could allow substrates bearing more reactive functional groups (such as esters and ketones) to be similarly converted. We here report our efforts to use different chiral lithium–zinc bases, made from a simple chiral lithium amide, ( R, R )- or ( S, S )-lithium bis(1-phenylethyl)amide (PEALi), for the enantioselective deprotonation of N, N -diisopropylferrocenecarboxamide. First, different zinc-based in situ traps were employed to intercept the formed ferrocenyllithium; optimization using enantiopure lithium bis[1-( S )-phenylethyl]amide (( S )-PEALi) led to the 2-iodo derivative in 96% yield and 69% ee in favor of the R P enantiomer. The method was extended to N, N -dimethylferrocenecarboxamide, morpholinoferrocenecarboxamide and N, N -diethylferrocenecarboxamide; for the latter, similar yield and enantioselectivity were recorded. DFT calculations on a model reaction showed very small differences between the activation energies leading to ( R P )- and ( S P )-2-lithioferrocenecarboxamides. Next, the behavior of various mixed amino-alkyl lithium zincates of the types R2 [( S )-PEA]ZnLi and R2 [( S )-PEA]2 ZnLi2 (R = alkyl) was studied, notably by varying the reaction temperature and time, and the amount of base. The best results were obtained with Me2 [( S )-PEA]2 ZnLi2, affording the 2-iodo derivative in 97% yield and 86% ee in favor of the S P enantiomer.